Molecular dynamics simulation of corrosion mitigation of iron in lead-bismuth eutectic using nitrogen as corrosion inhibitor. (May 2015) - Arkundato, Artoto; Su'ud, Zaki; Sudarko,; Hasan, Mohammad; Celino, Massimo
Abstract: The corrosion of structural materials used in fast nuclear reactor design is a current major problem. It is due to the use of liquid metal as a coolant candidate in the heat transfer system. The liquid metal as lead-bismuth eutectic was found to make high corrosion to structural material as steel. One of the solutions of this problem is to inject some inhibitor into liquid metal. In this current work we simulate the effect of nitrogen injection as inhibitor candidate. The simulation will predict the proper concentration of injected nitrogen and also observe the microscopic structure of the material before and after injection to know the ability of nitrogen as an inhibitor. The simulation follows the molecular dynamics method and for preliminary study we use iron material rather than steel. We also use lennard-jones potential for simplification of the study. It is from our simulation we see nitrogen shows better corrosion mitigation compare with oxygen as in our previous study. The effective inhibition can be achieved by injecting at least 0.056wt.% nitrogen. This amount seems to be able to reduce the corrosion level of iron till about 99.5% for high corrosion at temperature 750 °C.